PENGARUH PEMBERIAN PLANT GROWTH PROMOTING RHIZOBACTERIA (PGPR) AKAR PUTRI MALU TERHADAP PERTUMBUHAN DAN HASIL DUA VARIETAS KEDELAI (GLYCINE MAX. L) - HENNY RISANI PUTRI; NOVITA HIDAYATUN NUFUS; ANJAR PRANGGAWAN AZHARI (Universitas Mahasaraswati K. Mataram, 2024)
Lack of soil fertility causes a decrease in soybean productivity. One approach used to overcome this problem is to use PGPR, which are bacteria that can increase soil fertility by improving the availability of nitrogen and phosphate. This study aims to determine the effect of the right dose of shy daughter root PGPR fertilizer so that the growth and yield of two varieties of soybean (Glycine max L.) can be maximized and to find out what dose of shy daughter root PGPR fertilizer is appropriate to increase the growth and yield of two varieties of soybean (Glycine max L.). The experimental method was used in this study with experiments in the greenhouse The design used was a factorial completely randomized design (CRD) with two factors. The first factor is the application of PGPR with a concentration of 10% consisting of P0 (without PGPR), P1 (10 ml/plant) and P2 (20 ml/plant). The second factor is the variety consisting of (V1: Argomulyo Variety and V2: Dena 1 Variety). Data were analyzed using Analysis of Variance (ANOVA) and further tests with the Least Significant Difference Test (BNT) at the 5% level. The results showed that the best treatment was P0V1 for growth and P2V2 for yield